Antibacterial diketopiperazines from marine sponge-associated Actinobacteria against multidrug-resistant bacteria - AFINA LARASATI; SRI BUDIARTI; YULIN LESTARI (Society for Indonesian Biodiversity, 2025)
Abstract. Larasati A, Budiarti S, Lestari Y. 2025. Antibacterial diketopiperazines from marine sponge-associated Actinobacteria against multidrug-resistant bacteria. Biodiversitas 26: 6480-6489. The global rise of Multidrug-Resistant (MDR) bacterial infections has created an urgent demand for new antibacterial agents. Marine actinomycetes, particularly those associated with marine sponges, are considered a promising source of bioactive secondary metabolites. This study explored the antibacterial potential of 12 actinobacterial isolates obtained from the marine sponge Callyspongia sp., collected from the waters of Kepulauan Seribu, Indonesia. Among these, the isolate Cal24h exhibited the highest antibacterial activity. Based on previous 16S rRNA gene sequence analysis, this isolate was identified as Streptomyces tendae. Optimization of its culture conditions significantly enhanced inhibition zones against four MDR bacterial strains: 18.57±0.08 mm for Enteropathogenic Escherichia coli (EPEC) K1.1, 19.70±0.09 mm for Pseudomonas aeruginosa, 20.09±0.20 mm for Bacillus subtilis, and 20.54±0.31 mm for Methicillin-Resistant Staphylococcus aureus (MRSA). The Minimum Inhibitory Concentration (MIC) values of the ethyl acetate extract ranged from 62.5 to 125 µg/mL. Further analysis using GC-MS and LC-MS revealed the presence of diketopiperazine compounds, including Cyclo(Leu-Pro), Cyclo(L-Pro-L-Val), and Cyclo(Pro-Phe), all known for their antibacterial properties. Notably, this study is the first to report the use of a modified A1 medium to enhance antibacterial metabolite production in sponge-derived Streptomyces, representing a novel cultivation strategy. Cultivation in A1 medium yielded the highest extract quantity and exhibited the strongest antibacterial activity among all media tested. This study provides the first diketopiperazine production by S. tendae associated with the Indonesian sponge Callyspongia sp., thereby underscoring the untapped potential of sponge-derived actinobacteria as promising sources of antibacterial compounds against multidrug-resistant pathogens.